The Natural Product Butylcycloheptyl Prodiginine Binds Pre-miR-21, Inhibits Dicer-Mediated Processing of Pre-miR-21, and Blocks Cellular Proliferation. Issue 8 (15th August 2019) - Matarlo, Joe S.; Krumpe, Lauren R.H.; Heinz, William F.; Oh, Daniel; Shenoy, Shilpa R.; Thomas, Cheryl L.; Goncharova, Ekaterina I.; Lockett, Stephen J.; O'Keefe, Barry R.
Summary: Identification of RNA-interacting pharmacophores could provide chemical probes and, potentially, small molecules for RNA-based therapeutics. Using a high-throughput differential scanning fluorimetry assay, we identified small-molecule natural products with the capacity to bind the discrete stem-looped structure of pre-miR-21. The most potent compound identified was a prodiginine-type compound, butylcycloheptyl prodiginine (bPGN), with the ability to inhibit Dicer-mediated processing of pre-miR-21 in vitro and in cells. Time-dependent RT-qPCR, western blot, and transcriptomic analyses showed modulation of miR-21 expression and its target genes such as PDCD4 and PTEN upon treatment with bPGN, supporting on-target inhibition. Consequently, inhibition of cellular proliferation in HCT-116 colorectal cancer cells was also observed when treated with bPGN. The discovery that bPGN can bind and modulate the expression of regulatory RNAs such as miR-21 helps set the stage for further development of this class of natural product as a molecular probe or therapeutic agent against miRNA-dependent diseases. Graphical Abstract: Highlights: A screen to identify natural products that can bind regulatory non-coding RNAs Identification of natural pharmacophores that can bind precursor microRNA-21 Butylcycloheptyl prodiginine inhibits microRNA-21 and reduces growth of cancer cells Regulatory non-coding RNAs can be potential targets for small-molecule therapeutics Abstract : Matarlo et al. describe the identification of a natural product using a biophysical screen for small-molecule compounds that bind and modulate the stability of an oncogenic microRNA. The compound, butylcycloheptyl prodiginine, specifically binds to precursor microRNA-21 to inhibit its processing into the mature oncogenic miR-21 and selectively arrest growth of colon cancer cells.